Respuesta :

Answer:

x = -1 and y = -1

Step-by-step explanation:

Solve 3x+3y=−6;−x+y=0

Steps:

I will solve your system by substitution.

−x+y=0;3x+3y=−6

Step: Solve−x+y=0for y:

−x+y+x=0+x(Add x to both sides)

y=x

Step: Substitutexforyin3x+3y=−6:

3x+3y=−6

3x+3x=−6

6x=−6(Simplify both sides of the equation)

6x

6

=

−6

6

(Divide both sides by 6)

x=−1

Step: Substitute−1forxiny=x:

y=x

y=−1

Answer:

x=−1 and y=−1

if you isolate y in the bottom equation youll see that x=y so if you plug in y for x in the top equation youll get 6y=-6 then divide both sides by 6 to get y=-1 and since y=x x=-1

so it would be the last option where x and y both equal -1

ACCESS MORE